CRITICAL REVIEW OF LABORATORY TECHNICIAN CERTIFICATION EXAMINATIONS: ASSESSING VALIDITY, RELIABILITY, AND ALIGNMENT WITH INDUSTRY STANDARDS - HADEAL ALSHAMMRI, NOIR SAAD ALMOTAIRI, ALI MUQBIL A ALOTAIBI, FELWAH GASSEM ALOTAIBI, MALIYAH ALMUTAIRI, HATIM ABDULAZIZ ALOTAIBI, ABDUL AZIZ ABDULRAHMAN AL MEQBEL, ALI SALEH ALRUBUA (Chelonian Research Foundation, 2022)
Laboratory technician Certification examinations occupy the center stage in ensuring that professionals in this field are adept and knowledgeable about what they do. This essay summarizes the accuracy, precision, and relevance of such assessments concerning the real marketplace. The combined review of the literature and data from the monitored tests will answer the question of how efficient the present certificates are and how students understand the importance of these exams. This research piece could thus conclude the studies, then articulate the strengths and weaknesses of lab tech certification programs and suggest improvement by addressing the issues they do or don't cover so as not to leave any of their possible shortcomings unattended. Keywords: laboratory technician and certification tests that check the validity and reliability according to the industry standards provided.